Enhancing Mathematics Learning Outcomes on Fractions through the Use of Puzzle Media among Seventh-Grade Students at SMP IT Lentera - Septianingsih, Rika; Arcat, Arcat; Sohibun, Sohibun (Progressive of Cognitive and Ability, 2025)
Purpose – This study aims to investigate the effectiveness of puzzle media in improving mathematics learning outcomes on the topic of fractions among seventh-grade students at SMP IT Lentera. The research is motivated by the difficulties students often face in understanding fractions, which are considered abstract and challenging. Methodology – The study employed a Classroom Action Research (CAR) approach, conducted in two cycles consisting of planning, implementation, observation, and reflection. The participants were 30 seventh-grade students. Data were collected through tests and observations, and analyzed descriptively to examine learning outcomes and mastery levels. Findings – The results showed a significant improvement in student achievement. The average score increased from 60 in the pre-cycle to 72 in Cycle I and 82 in Cycle II. Classical mastery also rose from 40% to 66.7% and finally to 86.7%. These findings indicate that puzzle media is effective in making abstract mathematical concepts more understandable and engaging. Novelty – The originality of this study lies in the application of puzzle-based learning strategies to the teaching of fractions, which are usually perceived as difficult. Significance – The study provides practical implications for teachers seeking innovative strategies to enhance student engagement and achievement in mathematics learning.